1995
DOI: 10.1093/protein/8.5.497
|View full text |Cite
|
Sign up to set email alerts
|

In vivo system for the detection of low level activity barnase mutants

Abstract: We report the design of a new tightly controlled barnase system which allows the existence of the barnase gene in host cells without a signal sequence. When expression of barnase is turned on by gene inversion in vivo, the lethal effect of barnase (or its mutants) is not compromised either by coexpression of its polypeptide inhibitor (barstar), or by extracellular secretion. This serves as a rapid, sensitive in vivo test for the detection of any very low residual activity of the barnase mutants. Active-site mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…It has been previously reported that E. coli cells are able to tolerate low levels of barnase activity and have been used for in vivo assays of barnase mutant activities (Jucovic and Hartley, 1995;Axe et al, 1996;Yazynin et al, 1999). We demonstrated that the in vivo system reported in this paper was able to detect low levels of RNase activity of barnase mutants, and this system helped us identify mutants with sufficient activity to achieve high and consistent pollen ablation efficacy while minimizing any vegetative damage.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It has been previously reported that E. coli cells are able to tolerate low levels of barnase activity and have been used for in vivo assays of barnase mutant activities (Jucovic and Hartley, 1995;Axe et al, 1996;Yazynin et al, 1999). We demonstrated that the in vivo system reported in this paper was able to detect low levels of RNase activity of barnase mutants, and this system helped us identify mutants with sufficient activity to achieve high and consistent pollen ablation efficacy while minimizing any vegetative damage.…”
Section: Discussionsupporting
confidence: 51%
“…However, the in vivo comparison of barnase mutant activities in this study revealed that barnaseH102E had no detectable activity in the E. coli colony assay. Many single amino acid substitutions of the His at position 102 of the barnase protein have been reported, including substitution with Ala, Gln, Tyr, Asn, Asp, Arg, Lys, Gly, Leu, and Pro (Mossakowska et al, 1989;Meiering et al, 1992;Jucovic and Hartley, 1995;Axe et al, 1998). Among all the single substitution mutants listed above, only mutants carrying a substitution with Leu or Pro had detectable activities, while all others were found to render the enzyme inactive, including barnaseH102D.…”
Section: Discussionmentioning
confidence: 99%
“…The promoterless barnase gene is inserted with the complete barstar gene in the expression plasmid pMI43a in the antisense orientation to prevent a basal level of toxic barnase expression. When heat-induced, this vector will invert the barnase-barstar cassette and barnase will be transcribed by the tandem Ptac-lac promoters (13). Inversion is mediated by interaction between attP and attB sites derived from A phage (15).…”
Section: Introductionmentioning
confidence: 99%
“…Inversion is mediated by interaction between attP and attB sites derived from A phage (15). Since (13), that this mutation produces a barnase with residual RNase activity that is not properly inhibited by barstar and thereby limits growth. In the two-stage barnase expression system pMI43a-b (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, we introduced a strategy for producing soluble ICK proteins in Escherichia coli. 6 To this end, various ICK peptides were fused to the C terminus of the catalytically inactive H102A mutant of the RNase barnase from Bacillus amyloliquefaciens 7,8 separated by the four residue linker SSSM. Chemical cleavage with CNBr or enzymatic cleavage by thrombin allows isolation of the ICK peptide from the carrier protein.…”
mentioning
confidence: 99%